DECORATIVE AND PROTECTIVE TiN COATINGS ON 304 STAINLESS STEEL USING CATHODIC ARC PVD - Lyda, Sylwia (My University, 2016)
Titanium Nitride (TiN) coatings on the market today are known as very hard ceramic coatings most commonly deposited on metallic alloys such as stainless steel. Previous and current research into functional coatings demonstrated tremendous potential for various industrial applications. Primary focus in this research into TiN coatings is decorative coatings with scratch resistant properties specific to the cathodic arc PVD system used in this research. Individual parameters were varied while others kept constant prior to and during deposition. This created a unique set of samples in order to determine the most effective deposition recipe specific to the PVD system. Adhesion is a major factor to consider when developing coatings onto stainless steel. Two different cleaning methods are used to prepare the samples, one method being performed within a class 10,000 clean room. Initial research determined whether strong adhesion is dependent on external baking of stainless steel substrates by investigating various bake time and temperatures prior to deposition. Further research varied ion bombardment duration and voltage, TiN deposition duration, and nitrogen pressure and investigated their influence on scratch resistance and adhesion of the coatings. Scratch testing verified hardness and provided insight to the coating’s resistance to delamination with linearly increasing force. From these results, it became possible to identify the quality of adhesion between the TiN coating and stainless steel substrate.